Neuroplasticity-related correlates of environmental enrichment combined with physical activity differ between the sexes. - Kokras, N; Sotiropoulos, I; Besinis, D; Tzouveka, E L; Almeida, O F X; Sousa, N.; Dalla, C (Eur Neuropsychopharmacol, 2019)
Environmental enrichment (EE), comprising positive physical (exercise) and cognitive stimuli, influences neuronal structure and usually improves brain function. The promise of EE as a preventative strategy against neuropsychiatric disease is especially high during early postnatal development when the brain is still amenable to reorganization. Despite the fact that male and female brains differ in terms of connectivity and function that may reflect early life experiences, knowledge of the neural substrates and mechanisms by which such changes arise remains limited. This study compared the impact of EE combined with physical activity on neuroplasticity and its functional consequences in adult male and female rats; EE was provided during the first 3 months of life and our analysis focused on the hippocampus, an area implicated in cognitive behavior as well as the neuroendocrine response to stress. Both male and female rats reared in EE displayed better object recognition memory than their control counterparts. Interestingly, sex differences were revealed in the effects of EE on time spent exploring the objects during this test. Independently of sex, EE increased hippocampal turnover rates of dopamine and serotonin and reduced expression of 5-HT receptors; in addition, EE upregulated expression of synaptophysin, a presynaptic protein, in the hippocampus. As compared to their respective controls, EE-exposed males exhibited parallel increases in phosphorylated Tau and the GluN2B receptor, whereas females responded to EE with reduced hippocampal levels of glutamate and GluN2B. Together, these observations provide further evidence on the differential effects of EE on markers of hippocampal neuroplasticity in males and females.
Keywords: Animals; Cognition; Dopamine; Environment; Exploratory Behavior; Female; glutamic acid; Hippocampus; Male; Neuronal Plasticity; Phosphorylation; Physical Conditioning, Animal; Rats; Receptor, Serotonin, 5-HT1A; Receptors, N-Methyl-D-Aspartate; Recognition, Psychology; Serotonin; Sex Characteristics; Synaptophysin; tau Proteins